Animal Research that Respects Animal Rights: Extending Requirements for Research with Humans to Animals - Martin, Angela K. (Cambridge quarterly of healthcare ethics, 2022)
The purpose of this article is to show that animal rights are not necessarily at odds with the use of animals for research. If animals hold basic moral rights similar to those of humans, then we should consequently extend the ethical requirements guiding research with humans to research with animals. The article spells out how this can be done in practice by applying the seven requirements for ethical research with humans proposed by Ezekiel Emanuel, David Wendler, and Christine Grady to animal research. These requirements are (1) social value, (2) scientific validity, (3) independent review, (4) fair subject selection, (5) favorable risk–benefit ratio, (6) informed consent, and (7) respect for research subjects. In practice, this means that we must reform the practice of animal research to make it more similar to research with humans, rather than completely abolish the former. Indeed, if we ban animal research altogether, then we would also deprive animals of its potential benefits—which would be ethically problematic.